(untitled) (Journal of Preventive and Social Medicine, 2024)
Background: In the recent past, newly appeared emerging and re-emerging viruses causing unexpected illness and epidemics among humans, wildlife and livestock causing threat to the public health. During onset of any pandemic, there was always an embrace of conspiracy theory regarding the pandemic along with several misconceptions, misperception and stigma among the general population. The study aimed to assess the state of conspiracy belief regarding emerging viral infection among the healthcare professionals working in Combined Military Hospital (CMH) Dhaka. Methods: This cross-sectional study was conducted during July and September 2022 among conveniently selected 254 healthcare professionals working in CMH Dhaka. Data were collected through face-to-face interview using a pretested semi-structured questionnaire with validated and reliable tools. Results: Among the 254 respondents, 53.9% were male with a mean age (±SD) of 30.54 (6.36) years. More than twothird (72.8%) were graduate, married (62.6%), mostly Muslim (89.4%) and non-smoker (80.3%) with an average (±SD) monthly income of 83740.16 (57456.80). Highest (45.3%) of the respondents were permanently posted and only 33.5% attended any seminar/workshop/symposium in last six months. Job pattern (β=0.199, p<0.007) and attended any seminar/workshop/symposium (β=-0.149, p<0.01) were determined as significant predictors for conspiracy belief regarding emerging viral infection through hierarchical analysis. Marital status of the respondents was also identified as significant socio-economic issues conspiracy belief in emerging viral infection. Conclusion: The adoption of conspiracy belief regarding emerging viral infection demands appropriate public health intervention as well as awareness among the general population specially health care professionals as evident from our study. JOPSOM 2023; 42(1):1-6